2020
DOI: 10.7150/jca.42531
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the key genes and characterizations of Tumor Immune Microenvironment in Lung Adenocarcinoma (LUAD) and Lung Squamous Cell Carcinoma (LUSC)

Abstract: This study aimed to investigate the key genes and immune microenvironment involved in different TNM stages of lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC). The gene expression and clinical characteristics data were downloaded from the genomic data commons (GDC) database. After initial data processing, the characteristics of the immune microenvironment were analyzed. The differentially expressed genes (DEGs) in tumor vs. normal, and in early vs. advanced stages were screened, followed by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…The RYR3 gene encodes for a ryanodine receptor which mediates the calcium release for many cellular processes. Ryanodine receptor has been reported to be involved in epithelial-mesenchymal transition, in tumour cell apoptosis and treatment resistance in some cancers, including lung AC [46][47][48]. These data may provide the rationale for post-operative risk strati cation with a differential follow-up scheme.…”
Section: Discussionmentioning
confidence: 89%
“…The RYR3 gene encodes for a ryanodine receptor which mediates the calcium release for many cellular processes. Ryanodine receptor has been reported to be involved in epithelial-mesenchymal transition, in tumour cell apoptosis and treatment resistance in some cancers, including lung AC [46][47][48]. These data may provide the rationale for post-operative risk strati cation with a differential follow-up scheme.…”
Section: Discussionmentioning
confidence: 89%
“…Research has indicated that the TIME was closely related with the prognosis of cancers, including hepatocellular carcinoma ( Hu Z.Q. et al, 2020 ), lung adenocarcinoma, lung squamous cell carcinoma ( Zhang L. et al, 2020 ), and so on. Therefore, it is of great benefit to identify the vital potential biomarkers associated with the remodeling of the TME and prognosis, and develop more specific drugs against CC.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, TME was found to play a vital role in the initiation and progression of tumorigenesis [29][30][31][32] . Researches indicated that TIME was closely related with the prognosis of cancers, including hepatocellular carcinoma [33] , lung adenocarcinoma, lung squamous cell carcinoma [34] and so on. Therefore, it is of great bene t to identify the vital potential biomarkers associated with the remodeling of TME and prognosis, and develop more speci c drugs against CC.…”
Section: Discussionmentioning
confidence: 99%